ANALYZING TEXTUAL MEANING IN MAUDY AYUNDA'S G20 SPEECH AT PRESS CONFERENCE ON THE INTRODUCTION OF THE GOVERNMENT SPOKESPERSON: A SYSTEMIC FUNCTIONAL APPROACH FOR ELT MATERIALS - Putri, Alya Aqila; Saefullah, Hilmansyah; Wachyudi, Kelik (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
In the current era of globalization, the ability to speak English is becoming increasingly important in various fields, including politics, diplomacy, and education. This investigation uses the Len's systematic functionally method to try to explain the theme and rheme of Maudy Ayunda's spoken work.  Through the analysis of themes and rhemes in political and diplomatic speeches, this study aims to make a significant contribution to teaching English, especially by enriching teaching materials related to political and diplomatic speeches. Descriptive text employing Michael Halliday's SFL viewpoint technique is the study methodology employed. The speech given by Maudy Ayunda at a press conference regarding the appointment of the government spokesperson for Indonesia's G20 presidency serves as the study material. Through the analysis of themes and rhemes in speech sentences, this research assists students in understanding the structure and meaning of texts as well as improving their ability to understand, analyze, and respond to the texts effectively. The results of this investigation can be utilized for developing English teaching materials that facilitate understanding the meaning and context of texts. By understanding the use of themes and rhemes in political speeches, students can improve their ability to comprehend better, analyze, and respond to such texts. In teaching English, understanding themes and rhemes in political and diplomatic speeches holds significant value. Analyzing themes and rhemes helps students grasp the structure and meaning of texts, thereby enriching English language teaching materials related to the register of political and diplomatic speech.